Library Management system based on IoT - C.P, Mrs. Vandana; Bhattacharjee, Miss Anamika; Gupta, Miss Anubhuti (IJRDO -Journal of Computer Science Engineering, 2017)
Internet of things is an emerging technology which can and will lead to a better and dreamed future where maximum efficiency could be achieved with least efforts.The idea of the proposed system is provide an easy and user friendly library system to the users and at the same time to ensure a systematic approach towards library management so as to efficiently utilize the time and energy of the employees. Automation of library system is a convenient approach, as all the library devices can be managed from one place by implementing Internet of things (IOT).You are allowed to tap into high-tech functionality and luxury that wasn’t possible in the past in RFID.